Visual and Verbal Satire Style in Sebastian Tedy's YouTube Channel: A Multimodal Pragmastylistics Study - Nur Fithriyatul Chasanah; Riki Nasrullah (Raja Zulkarnain Education Foundation, 2026)
This study aims to examine the visual and verbal satirical language styles employed in Sebastian Tedy’s YouTube channel through a multimodal pragmastylistic analysis. The study focuses on the types of satirical language styles, multimodal forms, illocutionary speech acts, and language functions manifested in video blog utterances. This research applies a qualitative descriptive method, with data consisting of verbal utterances and visual elements containing satire. The finding demonstrate that the identified types of satire include irony, cynicism, sarcasm, satire, and innuendo, with cynicism emerging as the dominant type. The satirical expressions are realized through verbal monomodal, verbal-visual multimodal, and visual-verbal multimodal forms, with verbal elements predominantly functioning as the primary means of meaning construction. In terms of illocutionary speech acts, satire is primarily expressed through representative acts, followed by expressive, directive, commissive, and declarative acts. Furthermore, the language functions, identified encompass communicative, social, and ideological functions, which interact in constructing criticism toward consumerism, digital trends, lifestyles, and various social practices within society. The findings indicate that satire in digital media functions not merely as entertainment, but also as a linguistic strategy for implicitly conveying criticism through the integration of verbal and visual elements.